Islamic Banking Financial Inclusion and Tax Revenue in OIC Countries: To What Extent do They Correlate? - Muhammad Alan Nur; Annisa Rahma Febriyanti; Sulistya Rusgianto; Sri Herianingrum (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Tax revenue of Organization of Islamic Cooperation (henceforth OIC) countries has not reached the global average, and so has the financial inclusion. Notwithstanding this fact, few researchers have addressed the effect of financial inclusion on tax revenue in the context of Islamic finance while it is undeniably having significant connection to the real sector. Drawing on this crucial issue, the present study calls into the possible effect of Islamic banking financial inclusion on tax revenue in eleven countries of OIC membership consisting of Indonesia, Jordan, Kazakhstan, Kuwait, Malaysia, Nigeria, Oman, Pakistan, Saudi Arabia, Turkey, and the United Arab Emirates in the period of 2013 to 2019. The data were analyzed under the procedure of panel data regression using fixed effect model. The result depicted that Islamic banking financial inclusion, in terms of financial access and financial usage, had no significant effect on tax revenue of the OIC countries. This result is reasonable, since Islamic banking financial inclusion still requires massive promotion particularly by the OIC countries included in this study. Â Hence, this study leaves an implication for OIC countries to foster Islamic banking financial inclusion as a crucial effort to increase the tax revenue, in which Islamic banks play a promising role for sharia-compliance-based financial transactions in the recent years.